Infrared microspectroscopic imaging as a probing tool to fast distinguish chemical compositions in calcified deposits of prostatic calculi and calcific tendonitis. Issue 5 (2011) - Lin Lin, Shan-Yang Shan-Yang; Wu Wu, Tieh-Kang Tieh-Kang; Chiou Chiou, Hong-Jen Hong-Jen; Hsu Hsu, Ted Hueih-Shing Ted Hueih-Shing; Lin Lin, Chih-Cheng Chih-Cheng
Abstract : The specificity and homogeneity of the real compositional components within the calcified deposits of prostatic calculi and calcific tendonitis were investigated using Fourier transform infrared (FT-IR) microspectroscopy with or without automatic imaging system. The second-derivative analysis was also applied to differentiate the overlapping components of individual spectra for the calcified samples. The FT-IR microscopic imaging results of present study indicate that the complicated components such as protein, type B or type A carbonated apatite, brushite and calcium oxalate monohydrate were contained in the calcified tissue of prostatic tissue, but the protein, type A and type B carbonated apatites were mainly included in the calcific tendonitis. However, the traditional manually single-point FT-IR spectral result only reveals a little component contained in the calcified tissues, leading to an inaccurate diagnose of the complicated components in the calcified mixture.